Bimbingan dan Pelatihan Fermentasi Pakan untuk Budidaya Ikan Lele dengan Probiotik sebagai Upaya Peningkatan Hasil Produksi Masyarakat di Koto Luar, Kecamatan Pauh, Padang - Syafrizayanti Syafrizayanti; Rahmayeni Rahmayeni; Mai Efdi; Yeni Stiadi; Syukri Syukri; Yulia Eka Putri; Diana Vanda Wellia; Tio Putra Wendari; Admi Admi; Emil Salim; Geliz Luh Titisari; Famella Azhara (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
The use of feed in fish farming is often inefficient because fish only partially consume the feed spread in ponds, so it becomes waste for the aquatic environment and, even worse, will trigger new diseases. The Department of Chemistry's of Universitas Andalas team was trying to overcome this problem by increasing the efficiency of fish feed. For the feed to work optimally and produce good quality fish weight, it is necessary to modify the nutrition of the fish feed, one of which is by adding probiotics through a fermentation process. The method used in this activity includes training, mentoring, and demonstration plots in feed fermentation and counselling regarding the right time to feed. This activity targets fish farmers in the Koto Luar area, Pauh District, Padang, with a fish culturing group,